Implicações da inoculação com Azospirillum brasilense e de níveis de N em milho transgênico no cerrado - Queiroz, Isabel Dayane de Sousa (2014)
Maize is one of the cereals with greatest economical and nutritional importance. Its production is directly related to adequate supply of nutrients, especially nitrogen, which can be added by fertilization, or by its biological fixation. One of the most important nitrogen fixing microorganisms in grasses is Azospirillum sp., which, besides supplying nitrogen, improves root environment, increasing water and nutrient absorption by the plant. This study evaluated the efficacy of Azospirillum brasilense on transgenic maize development and yield under increasing levels of N. Two field experiments were done on adjacent areas in cropping season 2011/2012, on a savannah soil at the Experimental Farm Capim Branco, Uberlândia - MG. The experimental design was randomized blocks, with 6 replications. Treatments consisted of 5 N levels, and the lack or addition of Azospirillum brasilense, via seed treatment (100 mL ha-1, with minimum concentration of 2x108 CFU mL-1). Plant and ear insertion height, stalk diameter, fresh and dry matter of shoots, chlorophyll and leaf nutrient contents, kernel yield and percentage of rotten kernels were evaluated in both experiments. Maize plants responded significantly to nitrogen levels, both in the presence or obsence of Azospirillum brasilense. Addition of nitrogen fertilizers promoted greater plant height and stalk diameter. The presence of A. brasilense resulted in a linear response to N levels. Maize seed inoculation with Azospirillum brasilense improved nitrogen absorption efficacy by the plant. Increase in shoot fresh and dry matter, as a function of N levels, was greater in inoculated plants. Chlorophyll contents responded linearly to N levels, both in the presence or absence of Azospirillum. Rotten kernels incidence was not significantly affected by the application of different N levels. The weight of one thousand kernels responded linearly to nitrogen levels. Increment of Azospirillum inoculated plants was the double that of non-inoculated plants. Maize kernel yield responded positively to nitrogen fertilization up to 200 kg ha-1, presenting 12 t ha-1 in the presence of Azospirillum brasilense and 11 t ha-1 when it was not present. Inoculation with Azospirillum brasilense did not substitute the use of nitrogen fertilizers; however, it improved the efficacy of fertilization.